Analisis Penerapan Standar Operasional Prosedur Individual Check In Dan Check Out Oleh Resepsionis Di Vila De Umah Bali Eco Tradi Home - I Wayan Dedi Laksamana Putra; Ni Nyoman Nidya Trianingrum (Jurnal Mosaik Hospitaliti, 2026)
This study aims to analyze the implementation of Standard Operating Procedures (SOPs) in the individual check-in and check-out process by the receptionist at Vila De Umah Bali Eco Tradi Home. The issues examined include: (1) how the individual check-in and check-out SOPs are implemented, (2) what obstacles the receptionist faces in implementing them, and (3) how guests respond to the service. This study used a descriptive qualitative method. The research sample was determined using a saturated sampling technique due to the small population size, namely 15 individual guests who stayed during the data collection period. Data collection techniques included observation, interviews, documentation, and questionnaires. Data were analyzed descriptively to describe the implementation of the SOPs and the level of guest satisfaction. The results showed that the check-in and check-out SOPs were consistently implemented, despite operational constraints such as limited night staff and the absence of bellboys. The receptionist demonstrated a high level of understanding of the SOPs and was able to coordinate tasks with the night security guards. Based on the results of a questionnaire distributed to 15 guests, the satisfaction level with check-in and check-out services reached 95.06%, falling into the "Very Satisfied" category. The study concluded that the implementation of SOPs was effective and aligned with the villa's eco-friendly concept. Despite operational challenges, service remained efficient and met guest expectations.